Strategi Optimalisasi Adopsi Teknologi Sistem Barcode di Pt. Langkat Nusantara Kepong - Zulham; Lubis, Zulkarnain; Zarlis, Muhammad; Reza Aulia, Muhammad; Tanjung, Yulia Windi (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2023)
The research objective is to formulate a strategy for optimizing the adoption of barcode system technology by identifying internal strengths and weaknesses, as well as external opportunities and threats for oil palm plantation companies, especially PT. Langkat Nusantara Kepong (LNK). Data collection was done by distributing questionnaires, interviews and direct observation. The method used is descriptive qualitative and quantitative research methods. Analysis of research data using SWOT analysis. The results of the research based on the SWOT analysis show that the strategy that must be applied in the adoption of barcode system technology is the WO strategy with alternative strategies, namely increasing employee competence, motivation, and behavioral intention.